Adherence to iron folic acid supplementation and associated factors among antenatal CARE attending women in Sire district primary health care units, South-East Ethiopia: A facility based cross-sectional study - Abdela Edeo Berarti; Meless Gebrie; Bereket Beyene (Elsevier, 2023)
Background: Iron folic-acid deficiency anemia among pregnant women is a common public health problem in developing countries, particularly in low-income countries, and is associated with serious adverse health outcomes. Objective: This study aimed to determine the level of Iron-Folic Acid Supplementation (IFAS) adherence and associated factors among pregnant women in Sire District, Ethiopia. Methods: A facility-based study was conducted among randomly selected 345 pregnant women in Sire District. A structured and pre-tested interviewer-administered questionnaire was used to collect the data. EPI INFO7 was used to enter the data and export it to SPSS Version-21.0 for analysis. An AOR with a 95%CI was used to display the level of significance with a p-value of less than 0.05. Result: The overall adherence rate was 59.4%. Maternal information access [AOR = 2.49, 95%CI (1.21, 5.13)], knowledge on IFAS [AOR = 2.94, 95%CI (1.86, 4.62)], knowledge of anemia prevention [AOR = 2.56, 95%CI (1.40, 4.68)], medical advice during antenatal care [AOR = 10.7, 95%CI (2.33, 48.9)], anemia history [AOR = 15.2, 95%CI (8.69, 26.5)], and currently diagnosed anemia [AOR = 5.33, 95%CI (2.98, 9.57) had positively significant association. Whereas, having children [AOR = 0.57, 95%CI = (0.21, 0.70)] and awareness about iron-folic acid supplementation prevent low birth weight [AOR = 0.34, 95%CI = (0.19, 0.60)] had negatively significant association. Conclusion and Recommendation: The overall adherence was lower than WHO recommendations. Therefore, health workers regularly provide information for all antenatal care users about iron-folic acid supplementation and its adherence to preventing anemia and its consequence. MOH mobilizes the community for timely initiation and delivers comprehensive nutrition education to enhance adherence.